Pengaruh Kecerdasan Intrapersonal dan Kedisiplinan Belajar terhadap Prestasi Belajar Matematika - Farel Zefanya (Universitas Indraprasta PGRI, 2018)
The purpose of this study is to know: 1) the impacts of intrapersonal question and learning discipline on mathematics learning achievement all together.2) the impacts of intrapersonal question on mathematics learning achievement,3) the impacts of learning discipline on mathematics learning achievement. The methode used is correlational survey on the students of class x at SMK Raflesia Depok, at academic years 2015/2016. Sample is taken by simple random sampling technique from 40 respondents. Data collecting instrument used quisionaire for intrapersonal question and learning discipline and test instrument for mathematics learning achievement. Data is analyzed with test requirement analysis i.e normality test, linearity test and multicolineairity test. After test requirement fulfilled, the writer did inferensial analysis for hypothesis test by using double inferensial analysis. Based on the result show that: 1) there are impacts of intrapersonal question and learning discipline on mathematics learning achievement all together. 2) there are impacts of intrapersonal question on mathematics learning achievement. 3) there are impacts of learning discipline on mathematics learning achievement.